Nucleotide sequence of the DdeI restriction-modification system and characterization of the methylase protein. - Sznyter, L A (1987)
The DdeI restriction-modification system was previously cloned and has been maintained in E. coli on two separate and compatible plasmids (1). The nucleotide sequence of the endonuclease and methylase genes has now been determined; it predicts proteins of 240 amino acids, Mr = 27,808, and 415 amino acids, Mr = 47,081, respectively. Inspection of the DNA sequence shows that the 3' end of the methylase gene had been deleted during cloning. The clone containing the complete methylase gene was made and compared to that containing the truncated gene; only clones containing the truncated form support the endonuclease gene in E. coli. Bal-31 deletion studies show that methylase expression in the Dde clones is also dependent upon orientation of the gene with respect to pBR322. The truncated and complete forms of the methylase protein were purified and compared; the truncated form appears to be more stable and active in vitro. Finally, comparison of the deduced amino acid sequence of M. DdeI with that of other known cytosine methylases shows significant regions of homology.